2022
DOI: 10.3390/diagnostics12102429
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Cytomegalovirus Infection in Pregnancy

Abstract: The objective of this review was to bring to attention cytomegalovirus (CMV) infection during pregnancy, taking into consideration all relevant aspects, such as maternal diagnosis, fetal infection and prevention, prenatal diagnosis, and postnatal prognosis. A literature review was performed regarding adult and congenital infection. General information regarding this viral infection and potential related medical conditions was provided, considering the issues of maternal infection during pregnancy, transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…Furthermore, in a proportion of cases, herpesviruses may have been the (co‐)responsible agents causing rash, but only as a result of a reactivation induced by other causes, particularly other pathogens. Indeed, late primary infection with members of the family Herpesviridae seems to be unusual and reactivation can explain the peculiar HHV‐7 infection peak we found in older individuals 37,44,45 . Furthermore, several studies indicated the potential role of SARS‐CoV‐2 infection in the reactivation of human herpesviruses in latently infected host cells 46,47 .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, in a proportion of cases, herpesviruses may have been the (co‐)responsible agents causing rash, but only as a result of a reactivation induced by other causes, particularly other pathogens. Indeed, late primary infection with members of the family Herpesviridae seems to be unusual and reactivation can explain the peculiar HHV‐7 infection peak we found in older individuals 37,44,45 . Furthermore, several studies indicated the potential role of SARS‐CoV‐2 infection in the reactivation of human herpesviruses in latently infected host cells 46,47 .…”
Section: Discussionmentioning
confidence: 75%
“…Indeed, late primary infection with members of the family Herpesviridae seems to be unusual and reactivation can explain the peculiar HHV-7 infection peak we found in older individuals. 37,44,45 Furthermore, several studies indicated the potential role of SARS-CoV-2 infection in the reactivation of human herpesviruses in latently infected host cells. 46,47 While further research is needed to fully clarify the association between coinfections and skin rash in COVID-19 patients, our observation that 60% of SARS-CoV-2positive patients were also positive to one or more herpesviruses could be explained by herpesviral reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…The study led by Feenstra M. et al emphasizes the importance of maternal feelings of security and confidence in their maternal role, as they are closely connected to the process of becoming a mother [10]. High risk pregnancies increase the likelihood of complications and readmission for newborns [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, medical students should be aware that mononucleosis symptoms during pregnancy might be indicative of CMV infection. Hence, they will be able to early identify and manage the consequences of the infection the soonest possible ( 25 ).…”
Section: Discussionmentioning
confidence: 99%